THE INFLUENCE OF PHARMACOTHERAPY INTERVENTION ON PERCEIVED SOBRIETY IN REHABILITATION CENTER AND HOSPITAL IN WAKISO AND KAMPALA DISTRICTS, UGANDA. - Lindrio , Celestine; Dr. Kiyingi Pio Frank,; Dr. Nyende Paul , (Student's Journal of Health Research Africa, 2024)
Background Pharmacological therapies diminish the level of perceived sobriety, improve the quality of life, reduce intake and affect, demand for alcohol. Physicians prescribe medications for patients to manage withdrawals, foster sobriety, and decrease alcohol and other substance use. The study objective was to examine the influence of pharmacotherapy intervention on perceived sobriety in Butabika National Referral Hospital Kampala and Serenity Rehabilitation Center Wakiso Districts, Uganda to address the challenges of perceived sobriety. Methodology The study was guided by the post-positivist paradigm. The research adopted a cross-sectional research design with a mixed-method approach known as simultaneous triangulation. Using purposive sampling and simple random sampling, questionnaires and interview guides were used for data collection. 338 respondents participated in the study. SPSS was used for analyzing Quantitative data, and Pearson’s product-moment correlation coefficient was employed in testing the hypothesis. Primary data was collected using self – self-administered questionnaires, focused group discussions, observational checklists, and documentary reviews to obtain in-depth results. Results The results showed pharmacotherapy intervention and perceived sobriety r=0.723, which was positive with probability value p=0.000 < a=0.01 suggesting a significant correlation. Therefore, the stated Null Hypothesis was rejected which implies that pharmacotherapy intervention significantly positively correlates with perceived sobriety. “Most patients respond to Pharmacotherapy intervention, it controls withdrawal effects, alcohol addicts are given treatment (detoxification) at the initial phase, later are encouraged to attend group and individual counseling sessions to manage psychological challenges and social issues that may have led them into the use of alcohol”. Conclusion pharmacotherapy intervention has a significant positive correlation with perceived sobriety. Therefore, a change in pharmacotherapy positively affects perceived sobriety. Recommendation The study recommended that District Health Officers should encourage psychiatric doctors and nurses to understand that, one single intervention (pharmacotherapy) cannot facilitate long-term recovery but rather integrate with other recovery interventions.